Recent Developments in Pathological pH-Responsive Polymeric Nanobiosensors for Cancer Theranostics - Pramod Kumar, E. K.; Um, Wooram; Park, Jae Hyung (Frontiers in Bioengineering and Biotechnology, 2020)
Polymeric nanobiosensors (PNBS) that respond to tumor-related factors, including pH, have shown great potential for disease detection owing to their selectivity and sensitivity. PNBS can be converted into theranostic polymeric nanobiosensors (TPNBS) by incorporating therapeutic cargo, thereby enabling concomitant diagnoses and therapy of targeted diseases. The polymeric compartments in TPNBS play a significant role in the development and therapeutic efficacy of nanobiosensors. Polymers enhance the stability, biocompatibility, and selective or effective accumulation of nanobiosensors at desired pathological sites. The intrinsic pH sensitivity of either the polymers in TPNBS or the TPNBS themselves provides integrated potentialities such as cogent accumulation of TPNBS at the tumor, augmented tumor penetration, cellular uptake, and theranostic activation, including enhanced bioimaging signals and controlled release of therapeutics. In this review, we summarize recent developments in the design, preparation, and characterization of pH-responsive TPNBS and their ability to behave as efficient in vivo nanotheranostic agents in acidic cancer environments.